Some Properties and Application of the Extended Type I Generalized Logistic Distribution - Olapade, A. K. (2014)
In this paper, we present some results on properties of extended type I generalized logistic distribution of Olapade (2004). The mean, the median, the mode, the 100 k-percentage point of the distribution are presented. The study of order statistics is also considered in addition to the estimation of the parameters of the distribution and an application of the distribution to model a social data.